Improving Chemical Bonding Conceptual Understanding Using STAD Cooperative Learning Assisted by Interactive Media - Siong Tang; Lloyd Arvin Malalua (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to investigate the effectiveness of the Cooperative Learning model type STAD supported by interactive presentation media on students’ conceptual understanding of chemical bonding. Methodology: A quasi-experimental design with a non-equivalent control group was employed, involving two groups of secondary school students. The experimental group was taught using the STAD model integrated with interactive media, while the control group received conventional instruction. Data were collected through pre-test and post-test instruments, which were validated and tested for reliability. Main Findings: The results showed that the experimental group achieved a higher post-test mean score (82.13) compared to the control group (68.27), with an N-gain of 0.67 indicating medium–high improvement. Statistical analysis revealed a significant difference between the two groups (p < 0.05), confirming the effectiveness of the intervention. Novelty/Originality of this study: The novelty of this study lies in the integration of cooperative learning and interactive media with a specific focus on conceptual understanding in chemical bonding. These findings suggest that such an approach can significantly enhance students’ learning outcomes in chemistry education.